Characterization of oil extracted from whole grain flour treated with ozone gas. (January 2018) - Obadi, Mohammed; Zhu, Ke-Xue; Peng, Wei; Noman, Anwar; Mohammed, Khalid; Zhou, Hui-Ming
Abstract: We treated whole grain flour (WGF) with ozone gas applied at 5 g/h over intervals of 0, 5, 15, 35, and 45 min. We extracted oil from whole grain flour treated and untreated with ozone gas to investigate how the ozone affected the fatty acid composition. The fatty acid value decreased in the treated flour, whereas the peroxide and p -inisidine values increased with ozone gas treatment. The lipase activity was lower in oil extracted from the flour that had been ozonated for more than 35 min compared to the control sample. We also observed levels of oxidation in the volatile compounds heptanal, hexanal, tetradecane, decanal, 1-hexanol, and nonanal after ozone treatment. The oils extracted from the ozone-treated flour showed higher phenolic content and antioxidant activity. Highlights: We did the chemical and physicochemical properties of oil extracted from whole grain flour treated and untreated with ozone gas such as fatty acid composition, acid value, peroxide value, p -anisidine value, lipase activity and volatile compounds. We also have been analyzed the total phenols and antioxidant activities.